The Response of Duckweed (Lemna minor L.) Roots to Cd and Its Chemical Forms - Yan Xue; Jin-qin Wang; Jin Huang; Feng-ying Li; Ming Wang (Journal of Chemistry)
The response of duckweed (Lemna minor L.) roots to Cd and its chemical forms was investigated. The relative root growth rate and concentrations of Cd and its different chemical forms in the root, that is, ethanol-extractable (FE-Cd), HCl-extractable (FHCl-Cd), and residual fractions (Fr-Cd), were quantified. Weibull model was used to unravel the regression between the relative root elongation (RRL) with chemical forms of Cd. Parameters assessed catalase (CAT), peroxidases (POD), and superoxide dismutase (SOD), as well as malondialdehyde (MDA) and total antioxidant capacity (A-TOC). Our results show that both the relative root growth rate and relative frond number were affected by Cd concentrations. The chemical forms of Cd were influenced by Cd content in the medium. Relative root elongation (RRL) showed a significant correlation with chemical forms of Cd. Additionally, POD and SOD increased at lower Cd concentrations followed by a decrease at higher Cd concentrations (at more than 5 μM Cd). Moreover, MDA and A-TOC increased and CAT decreased with increasing Cd exposure. Furthermore, CAT showed a significant correlation with FHCl-Cd. Taken together, it can be concluded that the chemical forms of Cd are statistically significant predictors of Cd toxicity to duckweed and to the other similar aquatic plants.